Helichrysum × kani-isikii (Asteraceae), a new nothospecies from Turkey - Semi̇z Gürkan; Şenol, Serdar Gökhan; Günal, Batikan; Çi̇çek Mehmet; Eroğlu, Volkan (Phytotaxa, 2021)
In this study, Helichrysum × kani-isikii (Asteraceae), a new natural hybrid of H. compactum and H. unicapitatum from Babadağ (Denizli, Turkey), is described and investigated in detail for the first time. The new nothospecies is similar to H. compactum and H. unicapitatum, but it has some intermediate morphological and palynological properties that position it between the two putative parents. In the diagnosis of the hybrid, pollen size and shape were found as significant characteristics. Taxonomic, morphological, and palynological characteristics of H. × kani-isikii are compared with those of its putative parents, and some other details are presented with notes on the IUCN category and ecology of the nothospecies. In addition, a key to diagnosing the hybrid from its parental taxa is also provided.